Evaluating the effect of the plan of national syphilis control in controlling the syphilis epidemic in Jiangsu, China 2010–2020 - Shi, Lingen; Chen, Liping; Liu, Xiaoyan; Hu, Haiyang; Chen, Yuheng; Chen, Yunting; Zhang, Zhi; Zhou, Ying; Lu, Jing; Yang, Dandan; Guan, Wenhui (Frontiers in Public Health, 2023)
Background Starting in 2010, the Chinese government initiated a 10-year syphilis control plan, called the national syphilis control plan (NSCP), to address the emerging threat of syphilis. We aimed to evaluate the effect of the NSCP plan on syphilis control in Jiangsu, China. Methods The temporal trends of syphilis incidence, prevalence and rate of condom use were estimated by Joinpoint regression with average annual percent change (APC) and average annual percentage (APPC). A Chi-square test was conducted to analyze the outcomes in different subgroups. ArcGIS was used to analyze the spatiotemporal distribution of syphilis incidence. Results Geographically, early and congenital syphilis incidence decreased significantly in all areas of the province during the period of NSCP. Early syphilis incidence decreased from 21.1 to 8.8 (APC: −7.5, 95%CI: −8.6, −6.5, p < 0.001) per 100,000 people, and congenital syphilis decreased from 63.6 to 4.1 (APC: −14.8, 95%CI: −20.8, −8.4, p < 0.01) per 100,000 newborns from 2010 to 2020. Also, syphilis prevalence reduced from 13.4 to 3.8% (APC: −8.7, 95%CI: −12.1, −5.0, p = 0.001) among men who have sex with men, from 5.3 to 1.7% (APC: −7.9, 95%CI: −11.7, −3.8, p = 0.002) among female sex workers and remained under 1.0% with slight variations among pregnant women (APC: 0.3, 95%CI: −4.3, 5.1, p = 0.877) from 2010 to 2020. 0.2% (2,436) of pregnant women who received free syphilis testing during pregnancy were diagnosed with current syphilis infection, and 97.0% (2,555) of newborns in the province were delivered to women diagnosed with syphilis. 91.8% (2,346) of live babies and about 90% of diagnosed patients received complete standard syphilis diagnosis and treatment services. Conclusion Trends of early syphilis incidence and syphilis prevalence show a considerable decreasing trend among almost all the key populations after implementing NSCP. Congenital syphilis has significantly decreased as well and hence, the NSCP program should be sustained and strengthened to control the syphilis epidemic in China further.